Characterization of Kluyveromyces marxianus as a potential feed additive for ruminants - Nooraee, Seyed Eeman; Alimon, Abdul Razak; Ho, Yin Wan; Abdullah, Norhani (Wiley-Blackwell Publishing, 2010)
Aim: The aim of this study was to find suitable yeast isolates as potential microbial feed additives for ruminants. Methods and Results: Yeast isolates from traditional fermented food (tapai) and home-made wine were selected based on their tolerance to volatile fatty acids (VFA) mixture of acetic, propionic and butyric acids and to pH and temperature according to the rumen condition. The ability to grow in and produce ethanol was determined in yeast extract peptone glucose broth supplemented with a VFA mixture (VFA-YEPG medium). Fifty-five isolates showed OD660nm values between 0·35–0·6, and 27 isolates showed ethanol production in the range of 0·17–0·30% (v/v). All selected isolates were identified as Kluyveromyces marxianus base on biochemical tests (BioLog kit; Biolog Inc., Hayward, CA) and molecular techniques. The best isolate in terms of ethanol production (K. marxianus WJ1) significantly (P < 0·01) improved in vitro apparent dry matter (DM) digestibility of alfalfa (Medicago sativa), guinea grass (Panicum maximum) and timothy (Phleum pretense) hay by rumen microbes. Conclusion: Yeast isolates from tapai and wine were able to grow in VFA-YEPG medium, and K. marxianus WJ1 improved in vitro DM digestibility of plant substrates. Significance and Impact of the Study: This study indicated the possibility of using K. marxianus as a microbial feed additive.